Strategic priorities and accountability for allocating the state budget amid Covid-19 pandemic in Indonesia - Nanang Suparman (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
This study explains about strategic priorities of state financial management for handling the Covid-19 pandemic in Indonesia. The impact of this pandemic has caused the country’s financial posture in the state budget to be unbalanced, where receipts have decreased while in state spending has increased very sharply. Such conditions imply that the state budget deficit's widening exceeds the limit set by the law. The method used in this research method is a descriptive qualitative approach using literature data that can provide analysis of strategies to change the state financial management amid the Covid-19 pandemic. The study concluded that the government's strategic response in abnormal situations is an extraordinary matter with budget allocation priorities aimed at public health and safety, including medical personnel, protection and social safety nets for vulnerable people, and protection among business people. However, it requires accountable supervision, especially for the distribution of social assistance funds with experience prone to corruption practices so that it is not on target.